Supramolecular photochemistry: recent progress and key challenges. (4th November 2015) - Méndez-Ardoy, Alejandro; Bassani, Dario M.
Abstract : Supramolecular photochemistry has progressed enormously since it was first introduced thirty years ago. This article summarises the Closing Remarks from the Faraday Discussions on this topic, emphasising the recent progress made in the field as well as the key challenges that remain to be addressed. Specific examples in topical areas involving solar energy conversion, luminescent sensors, molecular logic and machines, and supramolecular photocatalysis are presented.